Long-term common trends in epifauna communities and associated demersal fish assemblages mediated by environmental and human stressors in the south-eastern North Sea - Anja Singer; Ingrid Kröncke; Kim E. Ludwig; Hermann Neumann; Anne F. Sell (Estuarine, Coastal and Shelf Science, 2025)

High-throughput differentiation of human blood vessel organoids reveals overlapping and distinct functions of the cerebral cavernous malformation proteins - Dariush Skowronek; Robin A. Pilz; Valeriia V. Saenko; Lara Mellinger; Debora Singer; Silvia Ribback; Anja Weise; Kevin Claaßen; Christian Büttner; Emily M. Brockmann; Christian A. Hübner; Thiha Aung; et al. (Angiogenesis, 2025)
Cerebral cavernous malformations (CCMs) are clusters of thin-walled enlarged blood vessels in the central nervous system that are prone to recurrent hemorrhage and can occur in both sporadic and familial forms. The familial form results from loss-of-function variants in the CCM1 , CCM2 , or CCM3 gene. Despite a better understanding of CCM pathogenesis in recent years, it is still unclear why CCM3 mutations often lead to a more aggressive phenotype than CCM1 or CCM2 variants. By combining high-throughput differentiation of blood vessel organoids from human induced pluripotent stem cells (hiPSCs) with a CCM1 , CCM2 , or CCM3 knockout, single-cell RNA sequencing, and high-content imaging, we uncovered both shared and distinct functions of the CCM proteins. While there was a significant overlap of differentially expressed genes in fibroblasts across all three knockout conditions, inactivation of CCM1 , CCM2 , or CCM3 also led to specific gene expression patterns in neuronal, mesenchymal, and endothelial cell populations, respectively. Taking advantage of the different fluorescent labels of the hiPSCs, we could also visualize the abnormal expansion of CCM1 and CCM3 knockout cells when differentiated together with wild-type cells into mosaic blood vessel organoids. In contrast, CCM2 knockout cells showed even reduced proliferation. These observations may help to explain the less severe clinical course in individuals with a pathogenic variant in CCM2 and to decode the molecular and cellular heterogeneity in CCM disease. Finally, the excellent scalability of blood vessel organoid differentiation in a 96-well format further supports their use in high-throughput drug discovery and other biomedical research studies.

Recent heavy metal pollution from the territory of the former Soviet Union (FSU): Ice core records and emission estimates - Anja Eichler; Petr Nalivaika; Sergey Kakareka; Tamara Kukharchyk; Theo M. Jenk; Thomas Singer; Tatjana Münster; Tatyana Papina; Stella Eyrikh; Andreas Plach; Margit Schwikowski (Science of The Total Environment, 2025)

Long-term response of coastal macrofauna communities to de-eutrophication and sea level rise mediated habitat changes (1980s versus 2018) - Anja Singer; Allert I. Bijleveld; Florian Hahner; Sander J. Holthuijsen; Krischan Hubert; Onur Kerimoglu; Loran Kleine Schaars; Ingrid Kröncke; Karsten A. Lettmann; Timo Rittweg; Gregor Scheiffarth; Henk W. van der Veer; et al. (Frontiers in Marine Science, 2023)
Since the last decades, previous long-term Wadden Sea studies revealed significant changes in the abundance, biomass and spatial distribution of characteristic macrofauna communities in response to environmental changes and anthropogenic stressors. In this study, we performed statistical community analysis for the East-Frisian Wadden Sea (EFWS, southern North Sea) on two reference datasets across a period with severe climatic and environmental changes (1980s-2018). Therefore, historical macrofauna data from the Quantitative Sensitivity Mapping (1980s, SENSI 1) were reanalyzed and compared with data from the Synoptic Intertidal Benthic Survey (SIBES/SENSI 3) collected in 2018. Our results revealed significant quantitative and spatial changes in the characteristic macrofauna communities between the 1980s and 2018, most likely in response to de-eutrophication and sea level rise mediated habitat changes. Since the 1980s, the total number of taxa remained relatively stable (1980s: 90, 2018: 81), but the total abundance decreased by ca. -31% and the total biomass decreased by ca. -45%, particularly in the eastern regions of the study site probably due to de-eutrophication processes. Thereby, the mean abundances/m 2 of ≥ -80% (1980s-2018) in the EFWS of several dominant species decreased: e.g. the gastropod Peringia ulvae , the polychaete Lanice conchilega and the bivalve Mya arenaria . In contrast, the mean abundance/m 2 of one dominant species increased by ≥ +80% (1980s-2018): the invasive bivalve Ensis leei . The mean biomass [g/m 2 ] of three dominant species decreased by ≥ -80% (1980s-2018): P. ulvae , L. conchilega and the amphipod Corophium volutator . In contrast, the mean biomass [g/m 2 ] of one dominant species increased by ≥ +75% (1980s-2018): the polychaete Arenicola marina . In the western part of the EFWS, not only higher abundances of A. marina, but also of L. conchilega and P. ulvae were found in 2018, caused i.a. by sea level rise mediated decreasing mud contents and sand accretion on tidal flats. At the community level, the Oligochaeta/Heteromastus community increased in spatial distribution in the western EFWS in 2018 in the vicinity of increasing mussel/oyster beds.

Small-scale distribution modeling of benthic species in a protected natural hard ground area in the German North Sea (Helgoländer Steingrund) - Lydia R. Becker; Alexander Bartholomä; Anja Singer; Kai Bischof; Susanne Coers; Ingrid Kröncke (Geo-Marine Letters, 2020)

Small supernumerary marker chromosomes (SMCs): genotype-phenotype correlation and classification - Heike Starke; Angela Nietzel; Anja Weise; Anita Heller; Kristin Mrasek; Britta Belitz; Christine Kelbova; Marianne Volleth; Beate Albrecht; Beate Mitulla; Ralf Trappe; Iris Bartels; et al. (Human Genetics, 2003)